Transport properties of crystallized antiferromagnetic MnBi2Te4 thin films grown by magnetron sputtering. (26th January 2023) - Lu, Haoyu; Huang, Yiya; Guo, Qixun; Wang, Kun; He, Miaomiao; Yin, Zhuo; Wang, Dongwei; Liu, Tao; Wang, Jing; Yu, Guanghua; Teng, Jiao
Abstract: The intrinsic magnetic topological insulator MnBi2 Te4 has drawn great attention due to its novel quantum states, among which the most promising one is the quantum anomalous Hall effect. However, MnBi2 Te4 is a metastable phase with a narrow temperature range for synthesis, which remains a challenge to grow uniform and high quality MnBi2 Te4 sample. Large-area MnBi2 Te4 thin films are mainly prepared by molecular beam epitaxy so far. Here, we report a highly versatile method for growing crystallized MnBi2 Te4 films on amorphous SiO2 /Si substrates by magnetron sputtering at room temperature and post-annealing. High-quality MnBi2 Te4 films with a c -axis perpendicular to the substrate and low surface roughness are realized. MnBi2 Te4 films have an antiferromagnetic Néel temperature of 21 K, with low carrier concentration (2.5 × 10 19 cm −3 ) and decent mobility (34 cm 2 V −1 s −1 ). The films reveal ferromagnetic at ground state and a typical spin-flop transition at 2–3 T. This work provides a pathway toward the fabrication of sputtered-MnBi2 Te4 devices for electronic and spintronic applications.